Aberrant NK cell profile in gestational diabetes mellitus with fetal growth restriction - Xiong, Yujing; Wang, Yazhen; Wu, Mengqi; Chen, Shuqiang; Lei, Hui; Mu, Hui; Yu, Haikun; Hou, Yongli; Tang, Kang; Chen, Xutao; Dong, Jie; Wang, Xiaohong; et al. (Frontiers in Immunology, 2024)
Gestational diabetes mellitus (GDM) is a gestational disorder characterized by hyperglycemia, that can lead to dysfunction of diverse cells in the body, especially the immune cells. It has been reported that immune cells, specifically natural killer (NK) cells, play a crucial role in normal pregnancy. However, it remains unknown how hyperglycemia affects NK cell dysfunction thus participates in the development of GDM. In this experiment, GDM mice were induced by an intraperitoneal injection of streptozotocin (STZ) after pregnancy and it has been found that the intrauterine growth restriction occurred in mice with STZ-induced GDM, accompanied by the changed proportion and function of NK cells. The percentage of cytotoxic CD27 -CD11b + NK cells was significantly increased, while the proportion of nourished CD27 -CD11b -NK cells was significantly reduced in the decidua of GDM mice. Likewise, the same trend appeared in the peripheral blood NK cell subsets of GDM patients. What's more, after intrauterine reinfusion of NK cells to GDM mice, the fetal growth restriction was alleviated and the proportion of NK cells was restored. Our findings provide a theoretical and experimental basis for further exploring the pathogenesis of GDM.